Genre-based approach possibilities in an English language course for brazilian adult learners - PEREIRA, Sávio Rafael Araújo (2024)
Language can be understood as a dialogic phenomenon that is fundamentally based on the discursive and interactional relationship between speakers (Voloshinov, 1986). In each context of human activity in which language is a constituent, it tends to settle into stable discursive forms, with specific conventions, which are called speech genres (Bakhtin, 1986). Thus, when considering the application of these ideas to the field of language teaching and learning, it appears to be pertinent to reflect on the importance of developing language education based on discursive practices (Cristovão, 2001). A possible answer to this issue is the adoption of genre-based approaches to language teaching (Swales, 1990; 1993; Hyland, 2004; 2007; 2019; Marcuschi, 2008; 2010; Tuan, 2011; Dirgeyasa, 2016). This work aims to investigate the effects of the implementation of genre-based approaches on an English as a foreign language course for adult learners. For this, we proposed this qualitative research to analyze the development of two genre-based lesson proposals and students’ final productions of genre exemplars. It was possible to observe the use of genre-based pedagogy in these English language classes brought several benefits in terms of lesson outcomes, such as students’ engagement in the class and the quality of the final productions. The experience also indicated to be advantageous for students' language learning process, who demonstrated the development of the expected understanding over the genres’ conventions.